Emerging Approaches of Bioremediation: A Comprehensive View - Sharma, Kanupriya (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 1&2 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Today, contamination of sites by uncontrolled discharge of pollutants due to rapid industrial growth and anthropogenic activities are causing ecological problems leading to imbalance in nature, is a global concern. In present scenario bioremediation is providing an eco- friendly option for environment betterment. This paper gives an overview of advancement clean-up techniques that have tremendous potential to degrade waste biologically using modified organisms and help in pollution abatement. How to cite this article: Sharma K. Emerging Approaches of Bioremediation: A comprehensive View. J Adv Res Alt Energ Env Eco 2018; 5(1&2): 33-36.